A systematic review on barriers and facilitators to physical activity interventions programmes among UK adults during COVID-19 pandemic - Johnson Mbabazi; Fiona MacGregor; Jeff Breckon; Barry Tolchard; Dorothy Irene Nalweyiso; George William Kagugube; Edward Kunonga; Mona Salman; Lawrence Achilles Nnyanzi (Taylor & Francis Group, 2024)
AbstractCOVID-19 was declared a global pandemic by the World Health Organisation in March 2022, resulting in over 115,0000 deaths worldwide by October of the same year. Only 25% of adults worldwide undertake the recommended levels of Physical activity (PA) for their respective age ranges, potentially exacerbating the symptoms associated with contraction of COVID-19 and recovery. This review aims to identify specific barriers and facilitators to engagement with PA interventions that were implemented during the pandemic. This quantitative study was undertaken adhering to the Preferred Reporting Items for Systematic Reviews and Meta Analyses. A systematic search was conducted of the following databases: CINAHL, MEDLINE, AMED, Cochrane, SCOPUS and Web of Science. Quality appraisal of selected papers was conducted through the CASP tool, with data extraction by two independent reviewers thereby minimising bias. This was then followed by a meta-analysis of the resulting data; however, no eligible studies were identified. Whilst 258 papers were identified through the database searches, following removal of duplicates (n = 19), the remaining 239 were screened, of these 237 were excluded on title and abstract, with the remaining two subsequently excluded following full read due to failure to meet the inclusion criteria. This review identified research gaps in the study.